Do contextual factors have a role in periodontal disease?. (22nd November 2016) - Sun, Xiangyu; Bernabé, Eduardo; Liu, Xuenan; Gallagher, Jennifer E.; Zheng, Shuguo
Abstract: Aim: To explore the association between contextual factors and periodontal disease. Methods: We pooled individual‐level data from 20, 204 35–44‐year‐olds and 9, 666 65–74‐year‐ olds, who participated in the 3rd National Oral Health Survey in China (2005), with province‐level data from different sources. The association of provincial macroeconomic factors [Gross Domestic Product (GDP) per capita and Gini coefficient], health resources (public health expenditure, dentist‐to‐population ratio and dental‐therapist‐to‐population ratio), demographic composition (proportion of rural population and minority ethnic groups) and tobacco industry (tobacco crops, cigarette production and proportion of smokers) with the numbers of teeth with periodontal pocket depth (PPD) ≥ 4 mm and loss of attachment (LOA) ≥ 4 mm were assessed in multilevel models, controlling for individual‐level demographic, socioeconomic and behavioural factors. Results: Only the proportion of smokers at province level was associated with the number of teeth with PPD ≥ 4 mm and only among senior adults. However, public health expenditure, dentist‐to‐population ratio and the proportion of minority ethnic groups were associated with the number of teeth with LOA ≥ 4 mm in both age groups. GDP per capita was also associated with the number of teeth with LOA ≥ 4 mm only among 35–44‐year‐olds. Conclusion: Contextual factors may contribute to periodontal disease and help explain geographical inequalities among Chinese adults.